Synthesis and characterization of potassium 1,3-bis(N-methylpiperazino)propan-2-O-xanthate and the complexes of Co(II), Ni(II) and Cu(I) ions - Goerguelue, Orhan A.; Arslan, Mustafa; Cil, Erol (Taylor & Francis Ltd, 2006)
Potassium 1,3-bis(N-methyl piperazino) propan-2-O-xanthate (LK), and its complexes with Co(II), Ni(II) and Cu(I) ions have been prepared and characterized as [CoL2(H2O)(2)], [NiL2(H2O)(2)] center dot 2H(2)O and CuL center dot 2H(2)O by FT- IR, H-1 and C-13 NMR spectroscopies, elemental analyses, magnetic susceptibility and TGA techniques.
Keywords: Co(II); Ni(II) and Cu(I) complexes; xanthate